Activated carbons treated with sulphuric acid: catalysts for catalytic wet peroxide oxidation - Gomes, Helder (2011)
Different liquid phase thermal treatments were applied to a commercial activated carbon (Norit ROX 0.8) in order to produce modified activated carbons with varying surface chemistry and increased acidic character. Chemical characterization of the prepared materials includes determination of the point of zero charge and evaluation of the concentration and nature of acidic and basic surface functionalities by acid/base titrations and temperature programmed desorption. The prepared materials were used as catalysts in the catalytic wet peroxide oxidation of the acid dye Chromotrope 2R in order to assess their removal efficiency. The relationship between the surface chemistry and efficiency for dye removal is discussed. As expected, decreasing acidity of the catalysts surface will correlate with increasing dye conversion. Unexpectedly, treatment with sulphuric acid leads to a very high yield of dye removal which falls out of the previous correlation. This was explained in terms of the introduction of sulphur containing groups on the carbon surface, which promotes the surface interaction between the pollutant and hydrogen peroxide: higher production of hydroxyl radicals close to the pollutant leads to improved dye removal. In addition, reutilization studies show that the catalyst prepared by sulphuric acid treatment is able to keep its performance in successive runs.